Acute toxicity of selected pesticides on the prawn Penaeus monodon - Joseph, K O; Gupta, B P; Krishnani, K K; Muralidhar, M (Indian Journal of Fisheries, 2011)
Static bioassay tests for acute toxicity of four pesticides on the prawn Penaeus monodon in brackishwater medium were conducted. The 96 h LC„ values of pesticides such as DDT, BHC(HCH), heptachlor and endosulfan were found to be 2.08, 4.10, 16.25 and 2.90 ppb respectively for prawns of size group 33- 46 mm. Admissible safe concentration for DDT, BHC, heptachlor and endosulfan were 0.21, 0.41,1.63, 0.29 ppb respectively. LCj, values were also calculated for each time interval and toxicity of the pesticides was compared using toxicity curves. Pesticides were not detected in creek and coastal waters.